A DECADE OF PUBLICATION ON TRUST AND THE LAW: A BIBLIOMETRIC ANALYSIS - Mohamed, Mazita; Mohd Arshad, ‘Ain Husna (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
This article presents a bibliometric analysis of trust and the law to understand how research in this area has expanded and changed during the past ten years. Data were collected through Scopus advanced search, resulting in a final dataset of 1,744 documents. These records were analysed using Scopus Analyzer for statistical trends, while OpenRefine was used to clean and harmonize key information. Visualisation of networks, including co-authorship, keyword co-occurrence and citation links, was produced through VOSviewer. The results show a steady growth of interest in trust and the law, marked by increasing attention to governance, transparency, digital technologies and institutional confidence. The analysis displays a rising trend in publications, dominance by jurisdictions such as the United States, the United Kingdom and China. Highly cited publications highlight concerns relating to artificial intelligence, ethical practices and the role of trust in public decision-making. Keyword mapping shows that trust has become strongly interdisciplinary, linking legal studies with policy analysis, ethics and emerging technological issues. The study offers a clear overview of existing knowledge and supports future work on the structure, application and challenges of trust within contemporary legal systems.